Antibacterial activity and mechanism of Stevia extract against antibiotic-resistant Escherichia coli by interfering with the permeability of the cell wall and the membrane - Chen, Xu; Yi, Lan-Kun; Bai, Yu-Bin; Cao, Ming-Ze; Wang, Wei-Wei; Shang, Zi-Xuan; Li, Jia-Jing; Xu, Mei-Li; Wu, Li-Fei; Zhu, Zhen; Zhang, Ji-Yu (Frontiers in Microbiology, 2024)
The present study was designed to compare the antibacterial activity of six chlorogenic acid (CA) isomers extracted from stevia and investigated the underlying antibacterial mechanisms involved. The results indicated that isochlorogenic acid C (ICAC) exhibited the strongest antibacterial activity against the tested bacteria, especially E. coli, at a 2 mg/mL minimum inhibitory concentration (MIC) and 8 mg/mL minimum bactericidal concentration (MBC). At the MBC, ICAC inhibited 72.66% of the clinical multidrug-resistant strains. Scanning electron microscopy (SEM) revealed that ICAC induced considerable morphological alterations in E. coli ATCC25922 and C4E2. The significant increase in the activity of extracellular alkaline phosphatase (AKP) indicated that ICAC damages the permeability of the bacterial cell wall. Additionally, the intracellular membrane (IM) permeability and the content of lipopolysaccharide (LPS), a main component of the outer membrane (OM), were determined. The significant decrease in LPS content and increased leakage of intracellular proteins and K + from E. coli indicated that ICAC could induce the exfoliation of OM and disrupt IM permeability, resulting in the loss of barrier function. The uptake of propidium iodide (PI), a compromised cell membrane nucleic acid stain, and confocal laser scanning microscopy (CLSM) further demonstrated that ICAC disrupted IM integrity. Moreover, the bactericidal effect and damage to bacterial microstructural function occurred in a dose-dependent manner. These data demonstrate that ICAC has excellent antibacterial activity and is a promising approach for overcoming the antibiotic resistance of pathogenic bacteria.